Analyzing the impact of climate change on rice production and strategies for enhancing efficiency, sustainability, and global food security - Algarni, Saeed Mohammed; Elshekh, Mohamed Ezzat; Agiza, Ahmed Mohammed Abou; Nassar, Farid Saber (International Journal of Innovative Research and Scientific Studies, 2025)
Climate change poses a significant challenge to rice production due to continuous shifts in temperature and rainfall patterns, along with extreme climatic events such as droughts and floods, which directly impact yield and crop quality. This study aims to analyze the impact of climate change on rice production and strategies for enhancing production efficiency, sustainability, and global food security. This study utilizes a qualitative descriptive research technique, focusing on analyzing the impact of climate change on rice production and developing effective strategies to enhance efficiency, sustainability, and global food security. The findings reveal a strong correlation between climate variability and declining rice yields, particularly in rain-fed regions, due to water scarcity, soil degradation, and increased pest infestations. To ensure the sustainability of rice production and enhance food security, the study recommends adopting effective adaptation strategies, including research and development of climate-resilient rice varieties, the application of precision agriculture technologies, and improved water resource management. Furthermore, the study emphasizes the importance of strengthening international cooperation and establishing supportive policies to assist farmers in adapting to climate challenges and ensuring the stability of global rice supply chains.